Cross-Border Effects of Fiscal Consolidations: Estimates Based on Narrative Records - Shafik Hebous; Tom Zimmermann (Center for Economic Studies and ifo Institute (CESifo), 2013)
We estimate cross-border spillover effects of fiscal consolidation episodes on output, bilateral trade flows, interest rate, and the exchange rate, employing the new IMF action-based fiscal consolidation data. Results indicate a negative effect of foreign fiscal consolidation policies on domestic output. Regarding the transmission mechanism, our results suggest that fiscal consolidations in foreign economies work their way into the domestic economy by negatively affecting exports. We do not find evidence for an interest rate channel. Trade effects are particularly pronounced for some European countries and are insignificant for others, such as the US and Canada. This is not due to the common currency or to differential specialization in trade.
Keywords: E62; F41; F42; F15; H50; H60; 330; fiscal consolidation; cross-border fiscal policy effects; fiscal adjustment; fiscal spillover